'Our kids don't want to eat taro anymore': Unravelling the challenges of contemporary sociocultural change in Niue. Issue 2 (1st November 2015) - Mcnamara, Karen E.; Lisimoni-Togahai, Birtha; Smith, Roy
Niue, an island country in the South Pacific Ocean, is commonly referred to as the 'rock of Polynesia'. The oval-shaped island is one of the world's largest coral islands and supports a population of 1, 460 residents. During focus group discussions with community members from three coastal villages in October 2012, it was evident that the country faces significant contemporary sociocultural changes that present numerous challenges for Niue's long-term future. The core challenges and concerns expressed by participants revolved around outmigration trends, a shift away from traditional subsistence living and increasing dependency on imported food, a decline in traditional practices, and the potential negative effects of a growing tourism industry. While these trends are largely well-known and well-documented for Niue, less attention has been given to how best to reconcile these concerns and the subsequent disjuncture between the 'problem' and 'solution'. This article therefore seeks to document these concerns, and importantly present a way forward for managing them in a way that will see a reversal or slowing of these currently perceived negative trends to ensure the long-term sustainability of Niue and its people.